The Extraterritorial Application of Federal Criminal Statutes: Analytical Roadmap, Normative Conclusions, and a Plea to Congress for Direction - O'Sullivan, Julie R (2018)
Under what circumstances can crimes that cross national boundaries be prosecuted in federal court? This question is critical given the increasing frequency with which criminal conduct crosses borders. This Article provides a guide through extant extraterritoriality analysis--warts and all--and then considers what the answer should be. First, this Article provides a step-by-step roadmap for those seeking to answer the questions of where a crime that spans borders was committed and, if it is deemed to have been committed outside the territory of the United States, whether the applicable statute and Constitution would countenance such a prosecution. This roadmap will reveal the myriad uncertainties and questions that confront courts daily. This Article resolves two of these doctrinal uncertainties: the continuing relevance of the Charming Betsy canon of construction and United States v. Bowman. Courts frequently invoke the Charming Betsy canon of construction to resolve extraterritoriality questions, but that canon is no longer relevant given the Supreme Court's latest cases. In those cases, the Supreme Court has applied a strong presumption against the extraterritorial application of federal statutes to conduct occurring outside the United States. Federal courts, however, rarely apply this presumption in criminal cases, instead regularly relying on a 1922 Supreme Court case, United States v. Bowman, to hold that federal criminal statutes have extraterritorial reach. But Bowman, given recent developments and viewed in light of the history of the Court's presumption, is an anachronism. Second, this Article rebuts the near universal conclusion, reached by both courts and commentators, that extraterritoriality analysis should be the same in civil and criminal cases. Fundamental separation of powers considerations and criminal law's foundational legality principle require that Congress, not courts, clearly and prospectively specify the content of criminal prohibitions. If there is ambiguity regarding whether a statute applies extraterritorially and in what circumstances, the operational arms of the legality principle, the rule of lenity, and (perhaps) the vagueness doctrine, demand that this ambiguity be resolved in favor of the defendant. In short, where a criminal statute is geoambiguous, a strong presumption against extraterritoriality ought to apply. These same principles do not apply in civil cases, and the rationales for the strong modern presumption that federal civil statutes do not apply to conduct beyond the boundaries of the United States advanced by the Supreme Court and scholars are not convincing. The current state of affairs--in which courts apply a strong presumption against extraterritoriality in civil cases but decline to do so in criminal cases--is, in short, profoundly wrong-headed. Congress ought to act promptly to enact a general provision that provides uniform guidance on these questions in criminal matters